KEBIJAKAN ATAS KEWAJIBAN E-FILLING DALAM PENYAMPAIAN SPT TAHUNAN BAGI ASN/TNI/POLRI DAPAT DITERAPKAN DI SELURUH WILAYAH INDONESIA - Sormin, Evan Hedi; Junawan, Junawan; Munthe, Desi Triana (Universitas Pembangunan Panca Budi, 2025)
The purpose of writing this Final Project is to find out the implementation of submitting individual SPT using E-Filing at the Medan Petisah Tax Service Office (KPP), to find out the progress of submitting individual SPTs, to find out the level of individual taxpayer compliance after using the E-Filing system in carrying out tax reporting. This study uses a descriptive method with data collection techniques through observation, interviews and literature at the research site, namely the Medan Petisah Tax Service Office (KPP). The results of this study indicate that the compliance of individual taxpayers in reporting the Annual Individual Income Tax (PPh) has increased, however, the tax office is still making efforts so that people are willing to report taxes so that income from the tax sector can increase.